Beyond value creation: exploring the importance of capturing the value of inclusion along different dimensions - Costa, Catarina Da Penha Gonçalves Belmar da (2022)
This work explores the characterization of the value of inclusion of people with disabilities in organisations. The concept of value is multifaceted and context-dependent, and there is actually little consensus on how to capture created value. Based on existing literature and qualitative analysis, findings suggest that, not only is the value of inclusion of people with disabilities in organisations closely aligned with the moral and economic dimensions of value, it seems that organisations have mechanisms for value creation and value capture, contributing to the strengthening of the strategic angle of inclusion in business.